METHODS OF TEACHING MEDICAL VOCABULARY IN RUSSIAN LANGUAGE LESSONS - Xaydarova Shoxista Rustamovna (Journals Park Publishing, 2024)
The article is devoted to the main specific ways of teaching foreign students medical and biological terminology of Russian language. Effective means of optimization in the process of training professional vocabulary at the lessons of Russian as a foreign language are identified.
Keywords: Terminology, term, terminological element, professional language, general vocabulary.